Market Making Contracts, Firm Value, and the IPO Decision - BESSEMBINDER, HENDRIK; HAO, JIA; ZHENG, KUNCHENG (Journal of Finance, 2015)
ABSTRACT We examine the effects of secondary market liquidity on firm value and the IPO decision. Competitive aftermarket liquidity provision is associated with reduced welfare and a discounted secondary market price that can dissuade IPOs. The competitive market fails in particular for firms or at times when uncertainty regarding fundamental value and asymmetric information are large in combination. In these cases, firm value and welfare are improved by a contract where the firm engages a designated market maker to enhance liquidity. Such contracts represent a market solution to a market imperfection, particularly for small, growth firms.